Effect of Potassium Fertilizer on Development of Bacterial Blight of Rice (Bangladesh Journal of Scientific and Industrial Research, 2011)
Effect of five potassium doses viz, recommended dose (RD) (40 kg Murate of Potash(MP)/hector), RD + 10 kg MP/ha, RD + 20 kg MP/ha, RD + 30 kg MP/ha, RD + 40 kg MP /ha to manage bacterial blight of rice were studied during Boro season in 2005. The experiment was laid in Randomized Completely Block Design (RCBD) having three replications. Highest disease severity (55.92%) was observed due to bacterial leaf blight at maximum tillering stage when applied 30 kg MP/ha additional potash. Lowest disease severity (0.45%) of bacterial leaf blight were recorded from the plot where no additional MP was applied but highest yield (4.35 tones/ha) was observed in the plot where additional 20 kg MP/ha was applied. The amount of potassium in the leaves did not vary significantly even after additional application of potassium either 30 or 20 kg MP/ha though it was more (1.31%) when applied 40 kg MP/ha. In another experiment in the present study the lowest disease severity 15.22% and 10.53% were recorded when additional 5kg MP /ha was applied seven days before inoculation at active tillering and panicle initiation stages, respectively. Disease severity was lower in single inoculation compare to multiple inoculations except the plot where 5kg/ha additional potash applied three days before bacterial inoculation. Maximum yield (3.86, 4.38, 4.64 t/ha) was recorded when inoculated at active tillering, panicle initiation and flowering stages separately if potassium was applied seven days before inoculation than those of multiple inoculations. The results suggested that potassium top dressing just before disease initiation was good for higher yield and less disease development. However inoculation in all the growth stages of the crop gave lower yields even potassium application was done at seven or three days before or after inoculation. Key words: Bacterial leaf blight; Oryza sativa L.; Potassium fertilizer DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8109 Bangladesh J. Sci. Ind. Res. 46(1), 69-76, 2011